Literasi Digital: Analisis Komentar Netizen Mengenai Penipuan Tiket Konser Coldplay - Zahirah Maulida, Siti; Nurhadi, Nurhadi (Universitas Muhammadiyah Sorong, 2025)
This paper examines netizens' responses on platform X to the discourse surrounding the Coldplay concert ticket fraud and its relevance to the four pillars of digital literacy promoted by the Ministry of Communication and Information (Kominfo). This study aims to identify netizen’s responses and understand digital literacy’s role in online communication. This research uses a qualitative approach with a constructivist paradigm, with data gathered from netizen’s comments on tweets related to ticket fraud. The results show a variety of reactions from netizens, ranging from empathy toward the victims to criticism of the system. Although digital literacy related to skills and security is relatively well implemented, while the aspects of digital ethics remains insufficient. The use of offensive language evidences this. The study concludes that raising awareness of digital ethics is crucial for creating a safer and more conducive digital space.